The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.67122
|View full text |Cite
|
Sign up to set email alerts
|

Sonication processing of mallow vinegar: effects on the bioactive compounds, amino acids, organic acid, sugar, mineral and microstructure

Abstract: This research was aimed with the objective of investigation the effects of sonication treatment on quality characteristics of mallow vinegar such as organic acids, sugar, amino acids, minerals, bioactive compounds, and microstructure. For the enhancement of bioactive components in mallow vinegar (Malva saylvestris L.), the response surface methodology (RSM) was employed using the central composite design to determine the combined effects of sonication treatment on the maximization of contents in vinegar. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
1
1
Order By: Relevance
“…The control and ornithine samples were higher than the TS-VJ samples. The result of alanine in our study was lower than that of the reported mallow vinegar samples [37].…”
Section: Amino Acidscontrasting
confidence: 95%
“…The control and ornithine samples were higher than the TS-VJ samples. The result of alanine in our study was lower than that of the reported mallow vinegar samples [37].…”
Section: Amino Acidscontrasting
confidence: 95%
“…There was no significant decrease in malic acid, tartaric acid, and citric acid content in TT-BGJ. Tokatli Demirok (2022), found similar effects for organic acid, and statistically significant differences were not detected (p > 0.05) in control and ultrasound-treated mallow vinegar [ 53 ]. There were no significant differences in the concentrations of organic acid in sonication-treated prebiotic cranberry juice [ 54 ], similar to our study.…”
Section: Resultsmentioning
confidence: 99%